Parental knowledge of nephrotic syndrome: A questionnaire based study - Guntupalli, Yashaswi; Kattula, Darshini; Mangipudi, Aruna; Tiruvalli, Snehitha; Obulreddy, Poojitha; Madala, Chandana Sree; Gaddam, Sri Lakshmi; Gutti, Viswaeswar Rao; Pavuluri, Aishwarya Lakshmi; Kandula Venkata, Koti Reddy; Rapur, Ram (Indian Journal of Child Health, 2025)
Introduction: When parents lack adequate knowledge about nephrotic syndrome, it can delay them from seeking timely medical attention. Unfortunately, many parents demonstrate insufficient understanding of effectively managing their children’s nephrotic syndrome at home. Aim: The purpose of the present study was to examine the parental knowledge of relapsing nephrotic syndrome and the effects of the gaps in this knowledge on the outcome of the nephrotic syndrome. Materials and methods: The present study was a prospective, questionnaire-based descriptive study that examined the parental knowledge of a paediatric patient with nephrotic syndrome. A second questionnaire study was conducted after parents received a pamphlet and an educational film in the vernacular language with information about nephrotic syndrome. Results: None of the parents had heard the diagnosis of nephrotic syndrome before it disturbed their child. The risk of one relapse was known to 85% of parents, but only 17.2 % of parents were informed that the child might have more than one relapse. The home monitoring for the urine albumin was not informed to 75% of parents. Accordingly, the majority did not perform home monitoring. The scholastic status of the mother emerged as the only significant risk factor (p = 0.035) that could influence the parental knowledge of relapsing nephrotic syndrome. Conclusion: Following this study, the department began disseminating educational materials (film on social media, booklet, fact sheet) in the local vernacular language for parents of children with nephrotic syndrome to improve accessibility.